Crosslinking of collagen using a controlled molecular weight bio-crosslinker: β-cyclodextrin polyrotaxane multi-aldehydes. Issue 57 (25th June 2015) - Liu, Sa; Xie, Renjian; Cai, Jie; Wang, Lin; Shi, Xuetao; Ren, Li; Wang, Yingjun
<x xml:space="preserve">Abstract</x> A novel bio-crosslinker which can improve the properties of collagen effectively.